Comparison of Metacognitions Between Obsessive Compulsive Disorder’s Subtypes and Normal Healthy Controls - Katre DOÐAN; Özgür Saygýn SOLAK; Kadir ÖZDEL; Mehmet Hakan TÜRKÇAPAR (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi, 2013)
Objective: The aim of the present study is to investigate metacognitive model between autogenous and reactive subtypes of OCD and also between total OCD group and healthy control group. Method: In the study, we included 61 patients who present to the Psychiatry Department of Ankara Dýþkapý Yýldýrým Beyazýt Hospital and 30 healthy individuals from the hospital staff as control group. Socio-demographic data form, SCID-I, SCID-II, Yale-Brown Obsessive Compulsive Scale (Y-BOCS) and the Metacognition Questionnaire (MCQ-30) were administered. Results: When we compared OCD and healthy control group, we observed significant statistical difference between two groups on the mean total and subscale scores of MCQ-30 (p<0.05), except for the subscale about positive beliefs about worry. When it comes to the MCQ-30 scores in autogenous and reactive subtypes of OCD, there was no significant statistical difference between the two groups (p>0.05) Conclusion: Similar metacognitive pathologies in the OCD subtype groups and the difference between OCD and the control group support the thought of using Metacognitive Therapy as a treatment option with no consideration of the subtype. However, the finding that there is no difference between subscale scores of positive beliefs about worry between OCD and healthy control group is a point that must be investigated. Yet, we need much more study about metacognitions in OCD. [JCBPR 2013; 2(1.000): 34-40]